Procedimientos ortodónticos mecánicos y no mecánicos en recidiva y retención. Revisión de cobertura temática (2020)
Introduction: stability after orthodontic treatment is an important goal for orthodontists. This issue has been highly important in orthodontics, so its progress and content require constant analysis. Methods: a panoramic and analytical review of citations and keywords from Web of Science helped create a body of information on the current advances in research on this field. Results: several fields of research arise from the analysis, dealing with surgery as an approach, molecular concepts, orthodontists’ experiences in professional practice, and the use of lasers and other applications. Conclusions: information on relapse and retention within orthodontics is still valid and requires further research on current issues to understand this complex phenomenon for both academia and clinical use.